Further Thoughts on a New Quota Formula, and Statistical Appendices I and II. (Policy Papers; Policy Paper ;, 2006)
The Board of Governors in a Resolution adopted on September 18 requested that the Executive Board reach agreement on a new quota formula, starting discussions soon after the Annual Meetings in Singapore. According to the Resolution, this work should be completed by the Annual Meetings in 2007, and no later than the IMFC Meeting in the Spring of 2008. The Resolution states that the new formula should provide a simpler and more transparent means of capturing members' relative positions in the world economy. This new formula would provide the basis for a second round of ad hoc quota increases, as part of the program of quota and voice reform to be completed by the Annual Meetings in 2007, and no later than by the Annual Meetings of 2008. This paper explores key issues related to a new quota formula as background for an informal Board seminar. This seminar is the first opportunity for the Board to discuss the new formula since the adoption of the Resolution. The paper first reviews the broad considerations and principles that should guide the design of a new quota formula, taking as a starting point the roles of quotas in the Fund. The paper also considers more specific issues in that light, such as the selection of variables and possible functional forms for the new formula. In examining these issues, the paper draws on the extensive discussion of the quota formulas in recent years, taking up questions raised both within the Board and in other fora.